Identification of Cancer Cell-Line Origins Using Fluorescence Image-Based Phenomic Screening - Lee, Jun-Seok; Kim, Yun Kyung; Kim, Han Jo; Hajar, Siti; Tan, Yee Ling; Kang, Nam-Young; Ng, Shin Hui; Yoon, Chang No; Chang, Young-Tae (PUBLIC LIBRARY SCIENCE, 2012)
Universal phenotyping techniques that can discriminate among various states of biological systems have great potential. We applied 557 fluorescent library compounds to NCI's 60 human cancer cell-lines (NCI-60) to generate a systematic fluorescence phenotypic profiling data. By the kinetic fluorescence intensity analysis, we successfully discriminated the organ origin of all the 60 cell-lines.
Keywords: PHENOTYPES; MOLECULES; PATTERNS; LIBRARY; CONTEXT; PROBE